Herpesviruses and breast milk - C. Pietrasanta; B. Ghirardi; M.F. Manca; S. Uccella; C. Gualdi; E. Tota; L. Pugni; F. Mosca (PAGEPress Publications, 2014)
Breast milk has always been the best source of nourishment for newborns. However, breast milk can carry a risk of infection, as it can be contaminated with bacterial or viral pathogens. This paper reviews the risk of acquisition of varicella-zoster virus (VZV) and cytomegalovirus (CMV), herpesviruses frequently detected in breastfeeding mothers, via breast milk, focusing on the clinical consequences of this transmission and the possible strategies for preventing it. Maternal VZV infections are conditions during which breastfeeding may be temporarily contraindicated, but expressed breast milk should always be given to the infant. CMV infection acquired through breast milk rarely causes disease in healthy term newborns; an increased risk of CMV disease has been documented in preterm infants. However, the American Academy of Pediatrics (AAP) does not regard maternal CMV seropositivity as a contraindication to breastfeeding; according to the AAP, in newborns weighing less than 1500 g, the decision should be taken after weighing the benefits of breast milk against the risk of transmission of infection. The real efficacy of the different methods of inactivating CMV in breast milk should be compared in controlled clinical trials, rigorously examining the negative consequences that each of these methods can have on the immunological and nutritional properties of the milk itself, with a view to establish the best risk-benefit ratio of these strategies before they are recommended for use in clinical practice.